Плагијаторство во научната работа - Трајковски, Владимир (Faculty of Philosophy, UKIM, Skopje, Macedonia, 2012)
In scientific writing, plagiarism is regarded as a serious breach of ethics. Plagiarism has different forms but can be categorized into two general distinct categories – plagiarism of ideas and plagiarism of text. The aim of the paper is to address plagiarism at length, to find ways to its disclosure and to make recommendations for its improvement. Authors have a responsibility to ensure that they make due acknowledgement every time they use the ideas or words of others. Editors of scientific journals also have a responsibility to discourage plagiarism. The most important steps in preventing plagiarism are those taken to address its causes. Plagiarism detection software has considerably affected the quality of scientific publishing. In Macedonian terms there is very little or no care for ethics in science. Often times we are witnesses of plagiarism that goes unpunished by the wider scientific community, nor the judicial authorities. In the future must be sanctioned and intellectual property must be respected. Creating software on Macedonian language that can detect duplicate publications is one of the possible solutions to overcome the bad situation of the scientific publications in Macedonia.
Plagiarism in scientific work
Keywords: плагијаторство, наука, публикации, списанија, уредници